PENGEMBANGAN BUKU AJAR NAHWU TSIMARUL JANIYAH BERBASIS MIND MAPPING UNTUK MENINGKATKAN QOWAID PADA SANTRI TPQ NURUL HIKMAH TANGGAN SRAGEN - Karyani Karyani; Siti Sulaikho; Rina Dian Rahmawati (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Teaching Arabic in madrasa education institutions is faced with several problems. Among them, students are less interested in understanding grammar, especially foreign languages, namely nahwu because Nahwu has too many vocabularies, even the number reaches more than 12 million words. This study aims to make it easier for students to learn the nahwu tsimarul janiyah book. This study uses a 4-D model by Thiagarajan. data collection resulted by observation, interviews, questionnaires, tests, documentation. The results of the validation of learning media from material experts show the number 93.3% and the validation from design experts shows the number 98.3%. Based on this, the qualifications of the media developed are very valid. The results of the instructional media design carried out by the researcher showed that learning using the mind mapping-based learning media of Nahwu Tsimarul Janiyah textbook in Nahwu learning was effective. This is evidenced by the sig value. (2 tailed) from Pretest and Postest is 0.00, the value of sig. <0.05 so it can be concluded that H0 is rejected, so there is a significant difference between pretest and posttest.